A cross sectional study of nutritional status among a group of school children in relation with gingivitis and dental caries severity - Harun Achmad; Andi M. Adam; Anni Satria (DiscoverSys Inc., 2016)
To determine nutritional status among a school children of Barru Regency, South Sulawesi, Indonesia, in relation with gingivitis and dental caries severity. Cross-sectional study. A total of 127 school children in the age range of 9-12 years from Barru Regency were included in this study as a sample of simple random sampling. Nutritional status of children (BMI index), degree of gingival inflammation (using chi-square test statistic), and missing teeth (DMF-T index) were recorded. Additional information was collected using a questionnaire survey regarding knowledge aboutÂ dental health, dietary habits, and oral health behaviors. The data were processed using the program Statistical Package for the Social Sciences (SPSS). A group of who severe underweight (102 children), had higher odds for mild gingivitis (GI 79.4%) than others group of who has an ideal weight (16 children), had mild gingivitis (GI 62.5%). Children, who severe underweight, had higher odds for moderate caries (38.2%) than others group of who has an ideal weight, had moderate caries (18.8%). Based on chi-square test, there are correlation of nutritional status and dental caries severity (p=0.000<p=0.05). There is a relationship of nutritional status with gingivitis and dental caries severity among a school children.